Two-step regulation by matrix Gla protein in brown adipose cell differentiation - Li Zhang; Xinjiang Cai; Feiyang Ma; Xiaojing Qiao; Jaden Ji; Jocelyn A. Ma; Laurent Vergnes; Yan Zhao; Yucheng Yao; Xiuju Wu; Kristina I. Boström (Elsevier, 2024)
Objective: Bone morphogenetic protein (BMP) signaling is intricately involved in adipose tissue development. BMP7 together with BMP4 have been implicated in brown adipocyte differentiation but their roles during development remains poorly specified. Matrix Gla protein (MGP) inhibits BMP4 and BMP7 and is expressed in endothelial and progenitor cells. The objective was to determine the role of MGP in brown adipose tissue (BAT) development. Methods: The approach included global and cell-specific Mgp gene deletion in combination with RNA analysis, immunostaining, thermogenic activity, and in vitro studies. Results: The results revealed that MGP directs brown adipogenesis at two essential steps. Endothelial-derived MGP limits triggering of white adipogenic differentiation in the perivascular region, whereas MGP derived from adipose cells supports the transition of CD142-expressing progenitor cells to brown adipogenic maturity. Both steps were important to optimize the thermogenic function of BAT. Furthermore, MGP derived from both sources impacted vascular growth. Reduction of MGP in either endothelial or adipose cells expanded the endothelial cell population, suggesting that MGP is a factor in overall plasticity of adipose tissue. Conclusion: MGP displays a dual and cell-specific function in BAT, essentially creating a "cellular shuttle" that coordinates brown adipogenic differentiation with vascular growth during development.